A New Genus and Species of Neotropical Horsefly (Diptera: Tabanidae) - G. B. Fairchild (Psyche: A Journal of Entomology)
The Neotropical Tabanidae are remarkable for the number of bizarre forms which have developed, especiaIly in the Tribe Diachlorini. Of the 146 generic names proposed at one time or another to include Neotropical Tabanidae, 65 were proposed for Diachlorini. The mortality rate among these names has been high, and conservative students of the family will probably recognize hardly half of these as useful. The proposal of another new genus in this fauna may thus appear somewhat foolhardy; nevertheless, the subject of this note presents a so far unique combination of characters which disturbs current ideas as to relationships within the Tribe.